The Aquilegia pubiflora (Himalayan columbine) mediated synthesis of nanoceria for diverse biomedical applications - Jan, Hasnain; Khan, Muhammad Aslam; Usman, Hazrat; Shah, Muzamil; Ansir, Rotaba; Faisal, Shah; Ullah, Niamat; Rahman, Lubna (RSC advances, 2020)
Herein, we report an eco-friendly, facile, one-pot, green synthesis of nanoceria for multiple biomedical applications. In the study, cerium oxide nanoparticles (CeO 2 -NPs) were synthesized using a simple aqueous extract of Aquilegia pubiflora as an effective reducing and capping agent. The biosynthesized nanoparticles were characterized via UV-vis spectroscopy, X-ray powder diffraction (XRD), high-performance liquid chromatography (HPLC), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Raman spectroscopy. The NPs were highly stable, exhibited high purity, and had a spherical morphology and mean size of 28 nm. FTIR and HPLC studies confirmed the successful capping of bioactive compounds on the nanoparticles. The well-characterized NPs were evaluated for a number of biomedical applications, and their antimicrobial (antifungal, antibacterial, and antileishmanial), protein kinase inhibition, anticancer, antioxidant, anti-diabetic and biocompatibility properties were studied. Our results showed that the Aquilegia pubiflora mediated CeO 2 -NPs were highly active against fungal strains, compared to the tested bacterial strains, with Aspergillus niger resulting in the largest zone of inhibition (15.1 ± 0.27 mm). The particles also exhibited dose dependent leishmanicidal activity with significant LC 50 values toward both the amastigote (114 μg mL −1 ) and promastigote (97 μg mL −1 ) forms of the parasite Leishmania tropica (KWH23). The NPs were found to be moderately active against the HepG2 cell line, showing 26.78% ± 1.16% inhibition at 200 μg mL −1 . Last but not least, their highly biocompatible nature was observed with respect to freshly isolated human red blood cells (hRBCs), making the greenly synthesized CeO 2 -NPs a novel candidates for multidimensional medical applications.